Restoring implant bed alveolar defect with autologous bone graft taken from the patient’s chin: a case report for the surgical procedure (Mustansiria Dental Journal, 2018)
Alveolar bony defects represent one of the most common problems that face oralsurgeons who practice dental implant placement. This case report describes amodification of a recent technique that aims to restore a bony defect in the implantsite using a cylindrical bone block autograft taken from the patient’s own chin; then tomake both clinical and radiographic evaluation of the prognosis periodically over sixmonths postoperatively. The technique was found to be effective and successful as atreatment option to restore implant site bony defects.